2022
DOI: 10.15252/emmm.202114764
|View full text |Cite
|
Sign up to set email alerts
|

THEM6‐mediated reprogramming of lipid metabolism supports treatment resistance in prostate cancer

Abstract: Despite the clinical benefit of androgen-deprivation therapy (ADT), the majority of patients with advanced prostate cancer (PCa) ultimately develop lethal castration-resistant prostate cancer (CRPC). In this study, we identified thioesterase superfamily member 6 (THEM6) as a marker of ADT resistance in PCa. THEM6 deletion reduces in vivo tumour growth and restores castration sensitivity in orthograft models of CRPC. Mechanistically, we show that the ER membrane-associated protein THEM6 regulates intracellular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Diagnostic biomarkers of LUAD and molecules should be identified for new therapeutic targets. Increased lipid uptake, storage, and lipogenesis occur in many cancers and increase tumor malignancy (29)(30)(31). Genes involved in lipid metabolism play a role in lipid metabolism reprogramming and drug resistance in tumors, making them potential targets for cancer therapy (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic biomarkers of LUAD and molecules should be identified for new therapeutic targets. Increased lipid uptake, storage, and lipogenesis occur in many cancers and increase tumor malignancy (29)(30)(31). Genes involved in lipid metabolism play a role in lipid metabolism reprogramming and drug resistance in tumors, making them potential targets for cancer therapy (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Both our study and this study have found low expression of THEM6 in some cancer tissues, but the significance of its low expression has not been studied yet. Recently, Blomme et al also found that THEM6 was highly expressed in prostate cancer and associated with poor prognosis [ 40 ]. Part of the reason for the interlaboratory variability regarding THEM6 findings and expression might be that there were heterogeneity and differences in biological behavior between different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Blomme et al (2022) show that THEM6 plays a critical role in ADT resistance by triggering ER stress response through preservation of ER membrane integrity, sterol biosynthesis, and ATF4 activation. To investigate the role of THEM6 in ADT resistance, the authors compared in vivo hormone naïve (HN) and castration‐resistant (CRPC) orthograft models of PCa by proteomics and found that THEM6 was significantly elevated in CRPC tumors.…”
Section: Figurementioning
confidence: 99%
“…In this issue of EMBO Mol. Med., the study by Blomme et al (2022) compared different in vivo models of ADT and identified thioesterase superfamily member 6 (THEM6) as a potentially clinically relevant protein overexpressed in CRPC. THEM (thioesterase superfamily member) are type II acyl‐CoA thioesterases (ACOTs) which are engaged in deactivation of fatty acyl‐CoA thioesters, generation of free fatty acids and CoA, regulation of intracellular fatty acid (FA) trafficking, and are an integral part of ER lipid homeostasis (Tillander et al , 2017).…”
Section: Figurementioning
confidence: 99%